Market shaping dynamics: interplay of actor engagement and institutional work. Issue 9 (24th September 2020) - Fehrer, Julia A.; Conduit, Jodie; Plewa, Carolin; Li, Loic Pengtao; Jaakkola, Elina; Alexander, Matthew
Abstract : Purpose: Combining institutional work and actor engagement (AE) literature, this paper aims to elucidate how the collective action of market shaping occurs through the interplay between market shapers' institutional work and engagement of other market actors. While markets are shaped by actors' purposive actions and recent literature notes the need to also mobilize AE, the underlying process remains nebulous. Design/methodology/approach: This paper is conceptual but supported by an illustrative case study: the Winding Tree. This blockchain-based, decentralized travel marketplace shapes a market by decoupling existing resource linkages, creating new ones and stabilizing others through a dynamic, iterative process between the market shaper's institutional work and others' AE. Findings: The paper develops a dynamic, iterative framework of market shaping through increased resource density, revealing the interplay between seven types of market shapers' institutional work distilled from the literature and changes in other market actors' engagement dispositions, behaviors and the diffusion of AE through the market. Originality/value: This research contributes to the emergent market shaping and market innovation literature by illustrating how the engagement of market actors is a fundamental means of market shaping. Specifically, it advances understanding of how market shapers' institutional work leads to new resource linkages and higher resource density in emergent market systems through AE. The resultant framework offers an original, critical foundation for future market shaping research.